AI as co-founder? : examining the role of AI in new venture teams - Fratini, Alberto (2025)
Artificial intelligence (AI) is rapidly transforming entrepreneurship, not only by optimizing workflows but also by reshaping how startups are founded and managed. This study explores how AI influences early venture processes, the extent to which it can be conceptualized as a co-founder rather than a tool, and the risks and challenges that accompany this integration. A qualitative approach was adopted to investigate these dynamics. Semi-structured interviews were conducted with 17 founders of early-stage ventures across diverse industries, primarily in Lisbon and Milan. The data were analyzed using the Gioia Methodology, enabling the inductive development of themes that capture how entrepreneurs perceive and implement AI within their ventures. The empirical findings reveal three major patterns. First, AI acts as an operational catalyst, accelerating development, experimentation, and productivity, and enabling compressed timelines. Second, the technology drives a reconfiguration of team structures and dynamics, allowing ventures to remain lean; hybrid decision-making processes emerge, where human judgment is combined with AI-supported reasoning, creating new forms of cognitive collaboration. Third, significant barriers and risks were identified, including technical implementation challenges, concentration of AI expertise in large corporations, and limited engagement with complex regulatory frameworks such as the EU AI Act. These findings point to a dual reality: while AI lowers traditional entry barriers, it also creates new dependencies and systemic vulnerabilities. Theoretically, the study extends entrepreneurship scholarship by challenging anthropocentric assumptions about founding teams. The findings suggest a need to conceptualize entrepreneurial agency as hybrid, distributed between humans and machines.